INDICATORS OF OVARIAL RESERVE, PRO- AND ANTIOXIDANT SYSTEM, CYTOKINE STATUS OF PERIPHERAL BLOOD AND PERITONEAL LIQUID IN PATIENTS WITH ENDOMETRIOID OVARIAN CYSTS - Ekaterina I. Sokolova; Irina I. Kutsenko; Elena I. Kravtsova; Saida K. Batmen (Кубанский научный медицинский вестник, 2019)
The aim of this work was to identify the characteristics of the cytokine status and state of the pro- and antioxidant systems in patients of late reproductive age with endometrioid cysts and determine their role in changing the ovarian reserve.Materials and methods. A total of 89 patients with endometrioid ovarian cysts (EOC) were examined. The control group consisted of 35 healthy patients admitted for surgical sterilisation. Peripheral blood was collected before surgery, while the peritoneal fluid collection was performed intraoperatively. In peripheral blood and peritoneal fluid, the level of cytokines was determined. The calculation of the anti-inflammatory index was performed, along with the evaluation of the content of lipid peroxidation products and the antioxidant activity. The analysis of the ovarian reserve parameters was conducted.Results. In patients of late reproductive age suffering from EOC, a decrease in the ovarian reserve is observed under the preserved hormonal background. The presence of EOC is accompanied by the activation of lipid peroxidation, both at the systemic and local levels, under a pronounced inhibition of the antioxidant defence link. At the systemic and local levels, patients with EOC experience an imbalance in the cytokine system with a significant activation of the pro-inflammatory component.Conclusion. The disruption of oxidative homeostasis and activation of immune inflammation, detected in patients of late reproductive age with EOC, may lead to the damage of the structural cell components of the functional ovarian tissue, thereby reducing the ovarian reserve.Conflict of interest: the authors declare no conflict of interest.